2017
DOI: 10.1177/1479164117731481
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared spectroscopy can detect differences in vascular responsiveness to a hyperglycaemic challenge in individuals with obesity compared to normal-weight individuals

Abstract: Near-infrared spectroscopy-vascular occlusion test technique was capable of detecting differences in vascular responsiveness during hyperglycaemia between normal-weight individuals and individuals with obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 41 publications
3
26
1
Order By: Relevance
“…Measurement of the sensitivity of STO 2 upslope has been well documented and supported in recent years, because NIRS is a low‐cost, easy‐to‐use methodology and has low test–retest variability both within and between days (McLay et al., ; Rosenberry et al., ; Soares et al., ). Soares et al () found that STO 2 upslope was positively correlated with %FMD of the brachial artery, a measure of cardiovascular health.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Measurement of the sensitivity of STO 2 upslope has been well documented and supported in recent years, because NIRS is a low‐cost, easy‐to‐use methodology and has low test–retest variability both within and between days (McLay et al., ; Rosenberry et al., ; Soares et al., ). Soares et al () found that STO 2 upslope was positively correlated with %FMD of the brachial artery, a measure of cardiovascular health.…”
Section: Discussionmentioning
confidence: 99%
“…the STO 2 reperfusion rate [STO 2 upslope (as a percentage per minute)] during PORH}. Research supports that NIRS, as a measure for microvascular responsiveness, is repeatable between trials (McLay, Nederveen, Pogliaghi, Paterson, & Murias, ) and sensitive to factors such as training (Soares, George, Proctor, & Murias, ), occlusion duration (McLay, Gilbertson, Pogliaghi, Paterson, & Murias, ), obesity (Soares & Murias, ), glucose load (Soares, Reimer, Alenezi, Doyle‐Baker, & Murias, ) and age (Rosenberry et al., ). Such findings support that NIRS coupled with PORH is an effective way to measure vascular health and assess the degree of vascular impairment in certain disease states.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…,; Soares et al. ; Soares et al., ). By using the NIRS‐VOT technique, muscle oxygen saturation (StO 2 ) can be measured and microvascular responsiveness can be assessed by calculating the steepness and the area under the curve of the overshoot of the StO 2 signal during re‐oxygenation.…”
Section: Introductionmentioning
confidence: 98%
“…Thus, properly assessing vascular function within conduit artery and the microvascular circulation is important for prevention, early detection, and monitoring of CVD . In relation to this, the use of near‐infrared spectroscopy (NIRS) combined with vascular occlusion test (VOT) technique (NIRS‐VOT) has been demonstrated to be a useful tool for assessment of microvascular function . This technique evaluates microvascular reactivity by assessing the steepness of the upslope of the muscle oxygen saturation signal (reperfusion slope, % per s), typically following a 5‐min period of limb occlusion .…”
Section: Introductionmentioning
confidence: 99%